The need for long-term ecological research in subterranean environments - Salvidio, Sebastiano; Rosa, Giacomo; Costa, Andrea (Ecological Questions, 2025)
Subterranean habitats, those found beneath the surface of nonmarine environments such as caves, aquifers, and other underground voids, are more widespread and ecologically significant than often assumed. These environments are functionally linked to the adjacent surface ecosystems, sharing hydrological, geochemical, and biological connections. Despite their global distribution and ecological importance, subterranean habitats remain among the least-explored and least-understood ecosystems. However, the scientific neglect of these environments is not limited to species inventories or basic ecological descriptions. This note highlights the near-complete absence of long-term ecological research (LTER) conducted on subterranean ecosystems. While LTER programmes are increasingly recognized as essential for understanding ecosystem dynamics, biodiversity trends, and the impacts of environmental change in terrestrial, freshwater, and marine systems, this kind of study appears to be extremely rare in subterranean environments. The lack of reference long-term studies hinders our ability to detect and interpret temporal changes in community composition, species interactions, and evolutionary processes within these unique environments. Nevertheless, there are compelling scientific reasons to promote the development of long-term ecological research in subterranean ecosystems. In fact, these simplified and relatively buffered habitats offer unique opportunities to study community interactions and adaptations under relatively stable climatic conditions. Furthermore, subterranean environments may serve as natural laboratories for investigating evolutionary processes such as ecological adaptation, morphological convergence, speciation and gene flow, especially when compared to the more variable surface environments with which they are functionally linked.